Lesions in sheep elbows: insights from a large-scale study - Holmes, M; Thomas, R; Hamerow, H (Elsevier, 2021)
Objectives Enthesophytes on sheep elbow joints are commonly reported in archaeological material. Although these lesions are often described as ‘penning elbow’, little is known of their aetiology. In this study, a new method for recording these lesions is presented, and the effect of age, sex and body size is explored to understand their potential for informing upon past human-animal interactions. Materials 1133 distal humerii and proximal radii from 16 archaeological sites. Methods The presence and severity of enthesophytes were recorded and findings compared with modern data from a group of 17 complete Soay sheep skeletons. Results Significant, positive correlations between age and body size and the presence of enthesophytes were demonstrated. Environmental factors and trauma may also play a role in their formation. Conclusion The aetiology of enthesophytes on sheep elbows is complex and varied, affected by age, body size and environment. Significance This is the first study of enthesophytes on sheep elbows to combine archaeological data with modern animals of known age and sex. Blanket explanations of husbandry methods for the cause of these lesions are dispelled, and use of the term ‘penning elbow’ is redundant. Limitations The sample of modern specimens is relatively small and would benefit from the inclusion of older individuals and those raised in different environments. Future research The method developed here can be adopted in future studies. Interpretations should take age, size and environmental factors into consideration, and only when these variables are established can the role of husbandry be evaluated.